Acute Pediatric Monteggia Fractures: A Conservative Approach to Stabilization. Issue 6 (September 2017) - Foran, Ian; Upasani, Vidyadhar V.; Wallace, Charles D.; Britt, Elise; Bastrom, Tracey P.; Bomar, James D.; Pennock, Andrew T.
Abstract : Background: In 2015, a multicenter study group proposed a treatment algorithm for pediatric Monteggia fractures based upon the ulnar fracture pattern. This strategy recommends surgical stabilization for all complete ulna fractures. The purpose of this study was to evaluate whether an initial nonoperative approach to pediatric Monteggia fractures resulted in poorer outcomes and a higher rate of complications. Methods: This institutional review board approved retrospective study evaluated all Monteggia fractures presenting to a level 1 pediatric trauma center between 2008 and 2014. Chart and radiographic reviews were performed on 94 patients who met inclusion criteria. The mean age was 5.5 years (range, 1 to 13 y). The mean clinical follow-up was 18 weeks. Major complications were defined as those requiring an unplanned second procedure (other than implant removal) or that may result in long-term disability (residual radial head subluxation/dislocation). Univariate ( P <0.05) and Multivariate Classification and Regression Tree (CART) ( P <0.05) analyses were used to identify variables associated with the need for surgical stabilization. Results: At final follow-up, there were no cases of residual radiocapitellar joint subluxation or dislocation and all fractures had healed. The majority (83%) of patients were successfully managed with a cast. Univariate analysis found Bado type and maximum ulna angulation as significant predictors ( P <0.05), whereas the CART analysis found ulna angulation >36.5 degrees as the only primary predictor of requiring surgical stabilization. Overall, good outcomes were achieved in all patients with few major complications. Conclusions: Although treatment algorithms are intended to minimize complications and maximize good outcomes, we believe that an unintentional consequence of the recently proposed pediatric Monteggia fracture treatment guideline may be the overtreatment of these injuries. In our cohort, the majority of patients were able to avoid the operating room and surgical implants without compromising outcomes or complications. This more conservative approach, however, requires close monitoring of patients in the first 3 weeks during which most reductions were lost. Level of Evidence: Level IV—therapeutic studies, case series.